Penetration testing : a guide for business and it managers. (BCS, 2019)
This essential guide for business and IT managers, developed in collaboration with CREST, explains the process of penetration testing and the benefits it brings. The book brings together a wide range of expertise, insight, and tips for setting up a penetration testing programme, maintaining it, and responding to the results of penetration tests.